(untitled) - Gunther, John (New York, 1962)
A survey of Europe in the early ’60’s, examining the differences between the Europe of today and that of twenty-five years ago and emphasizing the current political situation throughout the continent
Keywords: Europe,Châu Âu; Politics and government,Nhà nước và chính trị; 1945-